2013
DOI: 10.1364/boe.4.002066
|View full text |Cite
|
Sign up to set email alerts
|

Correction of image distortions in endoscopic optical coherence tomography based on two-axis scanning MEMS mirrors

Abstract: A two-axis scanning microelectromechanical (MEMS) mirror enables an optical coherence tomography (OCT) system to perform threedimensional endoscopic imaging due to its fast scan speed and small size. However, the radial scan from the MEMS mirror causes various distortions in OCT images, namely spherical, fan-shaped and keystone distortions. In this paper, a new method is proposed to correct all of three distortions presented in OCT systems based on two-axis MEMS scanning mirrors. The spherical distortion is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…First, the scanning MEMS mirrors are operated by using electrostatic [25][26][27][28][29][30][31], electromagnetic [22,32], or electrothermal [33][34][35][36][37][38][39] actuation. An electrostatic force between suspending and fixed electrodes induces the electrostatic actuation, which allows a high scanning resonant frequency but it often requires high operational voltages.…”
Section: Actuation Mechanism Of Microscannersmentioning
confidence: 99%
See 3 more Smart Citations
“…First, the scanning MEMS mirrors are operated by using electrostatic [25][26][27][28][29][30][31], electromagnetic [22,32], or electrothermal [33][34][35][36][37][38][39] actuation. An electrostatic force between suspending and fixed electrodes induces the electrostatic actuation, which allows a high scanning resonant frequency but it often requires high operational voltages.…”
Section: Actuation Mechanism Of Microscannersmentioning
confidence: 99%
“…The MEMS mirror scans 30° at DC 5.5 V voltage for both xand y-axes. Wang et al have demonstrated a 2D electrothermal MEMS mirror, which has four pairs of unique dual S-shaped bimorph structures [38].…”
Section: Actuation Mechanism Of Microscannersmentioning
confidence: 99%
See 2 more Smart Citations
“…Conventionally, this type of distortion was corrected using algorithms based on a point-to-point method [47,48], which can consume substantial computing resources. In reference [49], the authors discuss a new method that directly manipulates the original spectral interferograms in the phase domain to correct the spherical distortion. The algorithm continues with a Fourier transform and 3D geometrical transformation to correct fan-shaped and keystone distortions.…”
Section: Image Correctionmentioning
confidence: 99%